Analisis Corporate Governance Terhadap Manajemen Pajak Pada Perusahaan Sub Sektor Kosmetik dan Barang Kebutuhan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia - Pracita, Sriayu; Surianti, Kadek; Sahlan, Fahmi (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This research aims to determine the influence of management compensation, independent commissioners, and audit committees on tax management. Sample selection used the judgment sampling method with a total of 5 companies in the Cosmetic and Household Needs Sub-Sector listed on the Indonesia Stock Exchange that met the criteria. The analysis method in this study is panel data regression analysis. The research results indicate that the management compensation variable has a significant positive effect on tax management, independent commissioners have a significant positive effect on tax management, and the audit committee variable has a significant positive effect on tax management. Additionally, collectively, the variables of management compensation, independent commissioners, and audit committees have a significant positive effect on tax management.